Computational thinking in mathematics instruction integrated STEAM education: Global trend and students’ achievement in the last two decades - Suparman; Juandi, Dadang; Turmudi; Wahyudin (Beta: Jurnal Tadris Matematika, 2024)
[English]: Present study describes and synthesizes global trend and students’ CT achievement in mathematics instruction integrated STEAM education. A systematic review using bibliometric analysis and qualitative meta-synthesis was applied to do this study. Five hundred and nine studies indexed by Scopus and published between 2004 and 2023 were used as the data to bibliometric analysis. Particularly, 14 empirically qualitative studies were included in qualitative meta-synthesis. Results revealed that the publication development of CT studies slightly soared, whereas the citation development on CT studies relatively fluctuated in the period of 2004–2023. There were several emerging themes in CT studies, such as CT component, cognitive, affective, & psychomotor domain, mathematical content, CT learning environment, technological intervention in CT, research methodology, popular country involved in CT, participant, educational level, and STEAM component. Generally, students had achieved five CT components, such as pattern recognition, abstraction, decomposition, generalization, and algorithms caused by the integration of STEAM approach. The conclusion and implications of this study for mathematics education are comprehensively discussed. [Bahasa]: Studi ini mendeskripsikan dan mensintesis tren global dan pencapaian berpikir komputasi siswa dalam pembelajaran matematika yang menggunakan pendekatan STEAM. Sebuah riviu sistematik yang menggunakan analisis bibliometrik dan meta-sintesis kualitatif diterapkan untuk melakukan studi ini. Lima ratus sembilan studi inklusi yang terindeks Scopus dan dipublikasikan antara 2004 dan 2023 digunakan sebagai data untuk analisis bibliometrik. Secara khusus, 14 studi empiris kualitatif diinklusikan dalam meta-sintesis kualitatif. Hasil penelitian ini mengungkapkan bahwa perkembangan publikasi dari studi-studi berpikir komputasi cukup meningkat, sedangkan perkembangan sitasi terhadap studi-studi berpikir komputasi relatif berfluktuasi pada periode 2004–2023. Terdapat beberapa tema yang muncul terkait studi-studi berpikir komputasi, seperti: komponen berpikir komputasi, domain kognitif, afektif, dan psikomotor, konten matematika, lingkungan belajar berpikir komputasi, intervensi teknologi dalam berpikir komputasi, metodologi penelitian, negara popular yang dilibatkan dalam berpikir komputasi, partisipan, jenjang pendidikan, dan komponen STEAM. Secara umum, siswa sudah mencapai lima komponen berpikir komputasi, seperti: pengenalan pola, abstraksi, dekomposisi, generalisasi, dan algoritma yang disebabkan oleh pengintegrasian pendekatan STEAM. Simpulan dan implikasi dari studi ini untuk pendidikan matematika secara komprehensif didiskusikan.